Electron dropout echoes induced by interplanetary shock: Van Allen Probes observations. Issue 11 (7th June 2016) - Hao, Y. X.; Zong, Q.‐G.; Zhou, X.‐Z.; Fu, S. Y.; Rankin, R.; Yuan, C.‐J.; Lui, A. T. Y.; Spence, H. E.; Blake, J. B.; Baker, D. N.; Reeves, G. D.
Abstract: On 23 November 2012, a sudden dropout of the relativistic electron flux was observed after an interplanetary shock arrival. The dropout peaks at ∼1 MeV and more than 80% of the electrons disappeared from the drift shell. Van Allen twin Probes observed a sharp electron flux dropout with clear energy dispersion signals. The repeating flux dropout and recovery signatures, or "dropout echoes", constitute a new phenomenon referred to as a "drifting electron dropout" with a limited initial spatial range. The azimuthal range of the dropout is estimated to be on the duskside, from ∼1300 to 0100 LT. We conclude that the shock‐induced electron dropout is not caused by the magnetopause shadowing. The dropout and consequent echoes suggest that the radial migration of relativistic electrons is induced by the strong dusk‐dawn asymmetric interplanetary shock compression on the magnetosphere. Key Points: Shock‐induced dropout drift echoes of >300 keV electrons at L∼6 are observed for the first time The dropout is localized at duskside according to the energy dispersion of the echoes Such dropout echoes are not caused by magnetopause shadowing